Comparison of the effect of classic massage and aromatherapy on cardiac parameters in patients with cervical spine pain - Sadeck, Monika; Gębska, Magdalena; Weber-Nowakowska, Katarzyna; Garczyński, Wojciech; Kołodziej, Łukasz (Journal of Education, Health and Sport, 2017)
Admission: Chronic pain of the cervical spine is second, the lumbar pain, the most common symptom discomfort bone - joint experienced by patients. There are many methods of treatment, aimed at eliminating the symptoms associated with back pain. One of them is the massage. The aim of the study is to assess the impact of aromatherapy massages and classic parameters pressure and heart rate in patients with pain of the cervical spine. Material and methods: The study group has been acquired 46 people of both sexes aged 20 to 45 years with chronic pain of the cervical spine. The subjects were divided the two treatment groups. In Group Idonea series of 10 aromatherapy massages. In Group II conducted seriesę 10 classical massage. In each test was carried out standardized scale NDI. Before treatments and massages after a series of measurements were made in the level of intensity of pain NRS. Measurements of systolic and diastolic blood pressure and pulse rate were carried out before, immediately after and 5 minutes after the massage in 1, 5 and 10 day massage. Results: The data obtained suggest that aromatherapy massage showed a better analgesic effect. Classic massage showed a statistically significant decreasesystolic and diastolic pressure 5 minutes after the treatment (at 5 and 10 days of treatment) and after a series of massage (p <0.05). In Group I and II noted statistically significant (<0.05) drop in heart rate immediately after the massage only on day 1 of therapy. Conclusions: Classical massage treatments affect the changing parameters of blood pressure and heart rate immediately after the massage and 5 minutes after the massage. Aromatherapy massage exhibits superior analgesic effect than classic massage, what to look for when selecting treatment for patients with back pain.